Intervention with EMDR on a sample of healthcare workers in the nephrology and dialysis service during the COVID-19 emergency: from immediate treatment effect to long-term maintenance - Belvedere, Caterina; Fabbrini, Paolo; Alberghini, Elena; Ghedini, Simona Anna; Fernandez, Isabel; Maslovaric, Giada; Pagani, Marco; Gallina, Eugenio (Frontiers in Psychology, 2023)
Background During the COVID-19 pandemic, psychological support was provided to healthcare workers in Nephrology and Dialysis Operative Unit of the Azienda Ospedaliera Bassini using an EMDR group protocol to decrease posttraumatic stress symptoms in the medium and long term. The aim of this study was to demonstrate the effectiveness of EMDR treatment to reduce post-traumatic stress symptoms at the end of the first pandemic wave and its progress over time in the subsequent phases of the health emergency. Methods The sample of study consisted of 43 healthcare workers from the Nephrology and Dialysis Service who spontaneously decided to take part in the Brief EMDR treatment. Statistical analyses were carried out to compare the data collected with the IES-R, the Emotion Thermometer and the Post-Traumatic Growth Scale. The comparisons covered pre-treatment, post-treatment and follow-up. Results The results show a significant clinical improvement in reducing PTSD symptoms following the Brief EMDR group treatment. The comparison between PRE and POST treatment (DELTA1) regarding the scores from IES-R and Emotion Thermometer, highlighted the important statistically change that occurred in terms of symptomatology reduction (p < 0.001). By comparing POST and FU (DELTA2), it was observed that all variables except avoidance show a significant weakening of the effect with time (p < 0.001), but the magnitude of this effect is much smaller than the improvement found in DELTA1. DELTA 3 analysis finally made it possible to highlight how the treatment effect is maintained almost intact at follow-up. In fact, the maintenance of a better situation at follow-up was observed, in the course of re-traumatization linked to the new wave, compared to the initial data (p < 0.001). Conclusion The COVID-19 health emergency has significantly impacted hospital healthcare workers, leading to a high risk of developing PTSD symptoms. A psychological intervention aimed at the operators themselves is therefore of great importance.